Newsjacking : the urgent genius of real-time advertising - Hunter, Grant, ....- (London : Thames & Hudson, 2013)
From Grant Hunter and Jon Burkhart, the duo behind the Urgent Genius website, Newsjacking features over 100 examples of outstanding creative advertising from around the world that use topicality and viral techniques to communicate with audiences at high speed. Based on the themes and concepts the authors have devised through their groundbreaking research, Newsjacking combines principles and creative strategies with inspiring yet rapidly executed work to show how for advertising to be effective it has to move fast. Global brands are featured throughout and campaigns for Nestle, Puma, Samsung, Adidas, Heineken, Johnnie Walker and FIAT are included, among many others.
Keywords: Brands; Merken; Reclame : strategie